A Small Punch Test Method Application for the Evaluation of Reactor Pressure Vessel Material Properties Degradation - Jana Vaclavkova; Ludovit Kupca (Communications - Scientific letters of the University of Zilina, 2001)
In this paper we describe a new non-standard method for estimation of the reactor pressure vessel (RPV) materials mechanical properties by a small punch (SP) test. The great advantage of the SP test method is a low volume of test samples.Using this method it is possible to obtain the following data of basic mechanical properties: the yield stress and ultimate tensile strength, ductile-brittle transition temperature, the fracture toughness value.This method has been involved in the VÚJE project “New Surveillance Specimen Program for Jaslovské Bohunice V-1 nuclear power plant (NPP)” (NSSP). This paper describes the basic information about a testing procedure, metallographic preparation of test samples and comparison between results from standard tests and this new testing method.